2017
DOI: 10.1186/s13063-017-2347-z
|View full text |Cite|
|
Sign up to set email alerts
|

Adolescent Coordinated Transition (ACT) to improve health outcomes among young people living with HIV in Nigeria: study protocol for a randomized controlled trial

Abstract: BackgroundAdolescents living with HIV (ALHIV) have worse health outcomes than other populations of people living with HIV. Contributing factors include lack of standard and comprehensive procedures for ALHIV transitioning from pediatric to adult care. This has contributed to poor retention at, and following transition, which is problematic especially in high ALHIV-burden, resource-limited settings like Nigeria.MethodsUsing a two-arm cluster randomized control design, the Adolescent Coordinated Transition (ACT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The increasing availability and effectiveness of ART worldwide, has resulted in more children and adolescents living longer with HIV [7,8]. However, it is well-documented that adolescents struggle to initiate, remain engaged, and consistently adhere to ART [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing availability and effectiveness of ART worldwide, has resulted in more children and adolescents living longer with HIV [7,8]. However, it is well-documented that adolescents struggle to initiate, remain engaged, and consistently adhere to ART [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Among facilities surveyed across Nigeria, our study found routine practices bearing similarities to the major models of adolescent transition/transfer described in the literature [ 29 ]: transition between distinct pediatric and adult HIV providers and services; transition between the same providers/clinic with or without a family-centered approach, and transition utilizing adolescent transition clinics.…”
Section: Discussionmentioning
confidence: 80%
“…At the time of the survey, these HIV treatment centers catered to over 24,000 Nigerian ALHIV aged 10 to 19 years. The survey was conducted as a program evaluation as well as pre-study site assessments to inform the implementation of the Adolescent Coordinated Transition (ACT) study, a National Institutes of Health-funded study on adolescent HIV transitioning in Nigeria [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in sub-Saharan Africa have described NCD comorbidities in adults living with HIV [44,[109][110][111][112]. Besides mental health [113][114][115][116][117][118][119][120][121] and lung diseases [122][123][124][125][126], few studies have assessed the prevalence of NCDs and particularly NCD risk factors in AYLHIV in SSA other than as incidental ndings [127][128][129][130][131][132][133][134]. Risk behaviour research on AYLHIV in sub-Saharan Africa has predominantly focused on sexual risk behaviour [135].…”
Section: Discussionmentioning
confidence: 99%